Macedonia, Former Yugoslav Republic of : Analysis of the Agricultural Support Programs - World Bank (Washington, DC, 2014)
The report is structured to allow readers familiar with Macedonia s agriculture sector to quickly grasp the essentials needed to improve the sector, as well as to inform a general audience on how to address the challenges of a modern European Union (EU)-aspiring state. Chapter two provides an in-depth analysis of the sectoral background, illustrating the main characteristics and challenges of Macedonia s agriculture sector. The illustration takes an integrated approach to the sector, covering a vast range of inter-related topics including the prominence of the sector not only in terms of its economic and social contribution but also its implications for trade, the urban-rural poverty gap and shared prosperity, farm structure, climate adaptation, and capacity building. Chapter three draws on lessons from the European Union (EU) and provides a framework to analyze Macedonia s agricultural support programs. Further, the chapter provides a primer on the EU s Common Agricultural Policy (CAP) and its measures to support agriculture. Chapter four presents concise empirical evidence of the coverage and institutional capacity of the agricultural programs in Macedonia under both pillar one and pillar two measures. Chapter five then builds on the primary diagnostic set out in the previous chapters and critically examines the alignment of Macedonia s agricultural programs with the government s stated objectives of poverty reduction, competitiveness, and sustainable development. The results are at best mixed, suggesting substantial pathways for scaling up and exploiting untapped opportunities. Finally, chapter six synthesizes the overall evidence and presents policy implications and recommendations.